Circulating biomarkers in extremely preterm infants associated with ultrasound indicators of brain damage. (May 2018) - Leviton, Alan; Allred, Elizabeth N.; Fichorova, Raina N.; O'Shea, T. Michael; Fordham, Lynn A.; Kuban, Karl K.C.; Dammann, Olaf
Abstract: Aim: To assess to what extent the blood concentrations of proteins with neurotrophic and angiogenic properties measured during the first postnatal month convey information about the risk of sonographically-identified brain damage among very preterm newborns. Methods: Study participants were 1219 children who had a cranial ultrasound scan during their stay in the intensive care nursery and blood specimens collected on 2 separate days at least a week apart during the first postnatal month. Concentrations of selected proteins in blood spots were measured with electrochemiluminescence or with a multiplex immunobead assay and the risks of cranial ultrasound images associated with top-quartile concentrations were assessed. Results: High concentrations of multiple inflammation-related proteins during the first 2 postnatal weeks were associated with increased risk of ventriculomegaly, while high concentrations of just 3 inflammation-related proteins were associated with increased risk of an echolucent/hypoechoic lesion (IL-6, IL-8, ICAM-1), especially on day 7. Concomitant high concentrations of IL6R and bFGF appeared to modulate the increased risks of ventriculomegaly and an echolucent lesion associated with inflammation. More commonly high concentrations of putative protectors/repair-enhancers did not appear to diminish these increased risks. Conclusion: Our findings provide support for the hypothesis that endogenous proteins are capable of either protecting the brain against damage and/or enhancing repair of damage. Highlights: Angioneurins, proteins with neurotrophic and angiogenic properties can promote growth and maturation of brain cells. Angioneurins also have the capacity to protect against brain damage or enhance repair. Extremely preterm newborns with systemic inflammation can be at risk of ultrasound indicators of brain damage. High blood concentrations of angioneurins appear to modulate this risk. Paradoxically, high blood concentrations of some angioneurins can be associated with increased risk of brain damage.